Nutritional anemia and AIDS - Ruíz, Óscar (2003)
Objectives: To determine the type of anemia most frequent in patients with AIDS and the various degrees of anemia. Material and methods: One hundred patients 18 to 60 year-old infected with human immune deficiency virus (HIV) with residence in Lima and Callao were studied from January to December 2001 for blood count bone marrow aspiration, serum iron, transferrin, ferritin, folate and vitamin B12 levels. Samples were evaluated at the “Dos de Mayo” Hospital Clinical Pathology Department. Results: From the 100 patients, 60% had severe, 30% moderate and 10% light anemia; 70% nutritional and 30% due to chronic disease. In the nutritional anemia group, 25% was ferropenic anemia, 30% ferropenic and megaloblastic (double defect) and 15% megaloblastic. In the megaloblastic anemia group, 30 patients had folate deficiency and 15 vitamin B12 deficiency. Conclusions: Prevalent anemia was nutritional. Anemia’s degree was frequently severe.